Lines in the sand = Nga maenga o te one : the Native Land Court in the Southern Kaipara / Kaipara ki te Tonga and Tamaki Makaurau / Auckland : a reflexive reconsideration : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Philosophy, Massey University, October 1999 - Nightingale, Richard Beresford. (Massey University, 1999)
This thesis examines the alienation history of seven selected Kaipara ki te tonga/lower Kaipara and Tamaki Makaurau Auckland native/Maori land blocks under the regime of the land court from 1864 to the present. It has four parts. The introduction presents an over-view of the nature of the history production process in the context of the post-colonial poststructuralist/postmodernist age, the nature and scope of the thesis topic area and the rationale driving the choice of an unusual strategy to re-present the native land court alienation process in the seven specific land blocks. The theoretical perspective examines a variety of history-making strategies. An assessment is made of the suitability of modernist and poststructuralist/postmodernist approaches. The net outcome is a hybrid that combines the more appropriate aspects of each mode. An outline is given of a novel theoretical concept of the 'land-block-as-text.' This is predicated broadly on the experience of this unique Aotearoa/New Zealand geocultural unit and more specifically on the local and national historical import of the Orakei factor. It is postulated that Fenton's ideology for Orakei specifically and native land tenure generally became prescriptive texts. It argues that the conventional histories of each of the seven blocks highlight an aspect of the contextual/politics paradigm: namely, that the presence (and the absence of presence) of Eurocentric textual material is the driving imperative of the shape which these conventional histories take. Elements of the modernist approach together with the deconstructionist ploys of the poststructuralist/postmodernist schools are combined with more colloquial non-literate forms to suggest a new strategy. The issues of the goal of a multiplicity of voices, viewpoints, stories and methodologies mediated through one presenter are examined. An assessment is made of the appropriateness of placing so much omniscient variety under a single rubric. It is argued that on the one hand this form of history is more inclusive of all actors in the past-as-history. yet on the other dissipates the impact that a single authority might have. The main body of the thesis begins with a selective account of some politico-judicial and ethnographic aspect of probably the most significant foundational acts of the native/Maori land court system: the second Orakei title investigation, and the Fenton judgment of 1868/9. There follows the histories of six land blocks perceived through a critical prism. They are: Paeroa, Pukeatua. Tuparekura, Pukapuka, Paparoa and Orakei 4A2A. This substantial central section of the thesis incorporates two textualized forms: an introductory schedule in conventional chronicle format (annales) listing key facts and events of the alienation process for each block; and a new synthesis incorporating for each land block the history-making elements which are available for each block in order to indicate the nature of the historical problem at the land-face in a post-colonial age. For example, the alienation history of Paeroa is premised substantively on the administrative records of the colonial regime; that of Pukeatua outlines the unique nature of the 'ownership' under Native Land Court-awarded title and the way in which alienation proceeded following clarification of the legal position; that of Tuparekura examines the exceptional informal and 'extra-legal' nature of the alienation process; that of Pukapuka highlights two main points: that a legal vacuum prior to the award of clear Court title allowed informal alienation by lease from a local rangatira to a local speculator, and that following the award of Court-title to absentee Maori owners the lawyers moved in and carved up the block; that of Paparoa scrutinises in substantial detail the inexorable process of alienation over several decades by a strategy of 'divide and rule' using both legal and 'extra-legal' means; and that of Orakei 4A2A examines the contest of the last of the Tamaki Makaurau Maori non-sellers against the power of the Crown. A conclusion presents a summary of the significant patterns that emerge from the block histories and assess the efficacy of the theoretical strategy and methodology adopted in the thesis.
Keywords: Land tenure -- New Zealand; Kaipara District; Auckland; Maori (New Zealand people) -- Land tenure; New Zealand. Native Land Court.